Cross-cultural adaptation, validity, and reliability of the Child and Adolescent Behavior Inventory (CABI) for use in Brazil - Danielle S. Costa; Carlo Cianchetti; Deborah Dewey; Antônio Marcos Alvim-Soares; Iane Kestelman; Antônio Geraldo da Silva; Leandro F. Malloy-Diniz; Debora M. Miranda; Jonas J. de Paula (Elsevier, 2023)
Objective: The Child and Adolescent Behavior Inventory (CABI) is a cost-free 75 question-questionnaire developed by an Italian group to collect information from parents on the behavior of children and adolescents aged 6 to 18 years. It assesses different areas of children's behavior and psychopathology, including internalizing and externalizing symptoms, and can be used to identify children at risk of mental disorders both in clinical and epidemiological settings. In this study, the authors present a Brazilian-Portuguese adaptation of the CABI and its psychometric properties. Methods: First, the authors conducted a rigorous transcultural adaptation of CABI's questions and instructions for the Brazilian context. In an online sample of 598 parents, the authors found high reliability (internal consistency) for the CABI's main subscales. Results: Validity was supported by exploratory factor analysis (the authors found 6 factors representing several aspects of psychopathology both according to the DSM and HiTop models) and significant differences in most CABI's subscales between children with parent-reported psychopathology and typically developing ones. The present study suggests that the adapted version of CABI is a valid and reliable measure that can be used in Brazil. Conclusions: The CABI can be useful to the pediatrician to get fast but wide information from parents on the behavioral condition of their children or adolescents, and also to decide whether it is appropriate to consult a mental health professional.